2006
DOI: 10.1007/s11172-006-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Co(II)-Mediated and microwave assisted coupling between 2,6-diaminopyridine and nitriles. A new synthetic route to N-(6-aminopyridin-2-yl)carboximidamides

Abstract: The Chinese lantern type Co 2 (O 2 CBu t ) 4 {2,6 (NH 2 ) 2 C 5 H 3 N} 2 complex reacts with RCN (R = Me or Pr n ) under microwave irradiation (MWI) to give the mononuclear amidine complexes Co(O 2 CBu t ) 2 {H 2 N(C 5 H 3 N)NHC(R)=NH} (R = Me (4a) or Pr n (4c)). Under microwave irradiation, the addition of 2,6 diaminopyridine to acetonitrile in the presence of the pivalate complexes Co 2 (µ 2 OH 2 )(O 2 CBu t ) 4 (HO 2 CBu t ) 4 (1) or [Co(OH) n (O 2 CBu t ) 2-n ] x (2) afforded complex 4a in higher yield com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Even additional activation of the system with microwave irradiation did not lead to the formation of coupling products starting from mono amino derivatives of pyridines. 29 In the present study, we demonstrated that propiononitrile, which is electro philically activated through coordination to Pt IV in the trans [PtCl 4 (EtCN) 2 ] complex under mild conditions (30-35 °C) in anhydrous (to prevent hydrolysis of the starting platinum complex) dichloromethane, is involved in nucleophilic addition reactions with a number of 2 aminoheterocyclic derivatives, including monoamino pyridines. These reactions produced the hetarylamidine complexes trans [PtCl 4 {NH=C(Et)NHHet} 2 ] (1-5) (Scheme 1).…”
Section: Resultsmentioning
confidence: 63%
“…Even additional activation of the system with microwave irradiation did not lead to the formation of coupling products starting from mono amino derivatives of pyridines. 29 In the present study, we demonstrated that propiononitrile, which is electro philically activated through coordination to Pt IV in the trans [PtCl 4 (EtCN) 2 ] complex under mild conditions (30-35 °C) in anhydrous (to prevent hydrolysis of the starting platinum complex) dichloromethane, is involved in nucleophilic addition reactions with a number of 2 aminoheterocyclic derivatives, including monoamino pyridines. These reactions produced the hetarylamidine complexes trans [PtCl 4 {NH=C(Et)NHHet} 2 ] (1-5) (Scheme 1).…”
Section: Resultsmentioning
confidence: 63%
“…According to the X ray diffraction data, the complexes [(2,6 NH 2 ) 2 C 5 H 3 N] 2 Ni(η 2 OOCBu t ) 2 (3), [(2 NH 2 ) (6 Me)C 5 H 3 N] 2 Co(η 2 OOCBu t ) 2 (4), which was isolat ed with two benzene molecules of solvation (4•2C 6 H 6 ), [(2 NH 2 )(6 Me)C 5 H 3 N] 2 Ni(η 2 OOCBu t ) 2 (5), and [(2 NH 2 )C 5 H 4 N] 2 Co(η 2 OOCBu t ) 2 (6), which is isos tructural with the known cobalt derivative, 28 have similar molecular structures (Fig. 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…28- 30 The spectroscopic characteristics of the nickel containing complex [(2 NH 2 )C 5 H 4 N] 2 Ni(η 2 OOCBu t ) 2 (7) are similar to those of cobalt analog 6 characterized by X ray dif fraction. 28 In the crystal structures of 3-5, there are intermolec ular hydrogen bonding between the hydrogen atoms of the amino groups of the pyridine ligands and the oxygen at oms of the carboxylate groups. In the crystal structures of (8) or Ni (9), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of the ligands and complexes was studied. Additionally, the Chinese-lantern-type Co 2 (O 2 CBut) 4 {2,6-(NH 2 ) 2 C 5 H 3 N} 2 complex reacted with RCN (R = Me or Pr) under microwave irradiation to give the mononuclear amidine complexes Co(O 2 CBut) 2 {H 2 N(C 5 H 3 N)NHC(R):NH} (R = Me or Pr) (Bokach et al, 2006). Al-containing mesoporous silicates (Al-MCM-41 and Al-HMS) supported Mn(salen) catalysts were prepared by three different methods: impregnation of salen ligand and support with dichloromethane and then irradiated by microwave (method A), direct solidstate interaction between salen complex and support under microwave irradiation (method B), as well as the conventional ion exchange (method C) (Yin et al, 2005;Zhang et al, 2003).…”
Section: Complexes With No-containing Ligandsmentioning
confidence: 99%